Promyelocytic Leukemia Restricts Enterovirus 71 Replication by Inhibiting Autophagy - Chen, Deyan; Feng, Chunhong; Tian, Xiaoyan; Zheng, Nan; Wu, Zhiwei (Frontiers in Immunology, 2018)
The PML (promyelocytic leukaemia) protein, also known as TRIM19, functions as a major organizer of PML nuclear bodies (NBs) in most mammalian cells and plays important roles in antiviral activities against both DNA and RNA viruses. In the current study, we found that the downregulation of PML rendered HeLa cells more susceptible to infection by enterovirus 71, and the overexpression of the PMLIII or PMLIV isoforms inhibited viral protein expression and resulted in viral titres that were 2 to 3 log units lower than in the control. Using short interfering RNAs, the downregulation of either the PMLIII or PMLIV isoform increased both viral protein VP1 expression and viral production. The PML repression of EV71 replication was partially mediated by the inhibition of autophagy, and PML deficiency triggered autophagy. Furthermore, the EV71 infection resulted in a reduction in PML independent of the proteasome pathway. Instead, PML degradation was mediated by virus protease 3Cpro during the viral infection. In conclusion, PML contributes to a cellular antiviral effect by inhibiting autophagy, which is countered by a disruption of PML-NBs mediated by viral protease 3Cpro.